Role of Whole-Spine Screening Magnetic Resonance Imaging Using Short Tau Inversion Recovery or Fat-Suppressed T2 Fast Spin Echo Sequences for Detecting Noncontiguous Multiple-Level Spinal Tuberculosis - Siddiqui, Mohammed Azfar (Asian Spine J, 2018)
STUDY DESIGN: Retrospective review. PURPOSE: The purpose of the present study was to evaluate the role of whole-spine screening using short tau inversion recovery (STIR) or fat-suppressed T2W fast spin echo (FSE) sequences in patients with spinal tuberculosis (TB). OVERVIEW OF LITERATURE: The identification of noncontiguous multiple-level spinal tuberculosis (NMLST), symptomatic or not, is important because of its management implications. Most centers do not perform routine whole-spine magnetic resonance imaging (MRI), and the reported incidence of NMLST varies from 1.1% to 74.1%. METHODS: We completed a retrospective review of clinical and radiographic data of 365 patients with spinal TB who presented at Jawaharlal Nehru Medical College, Aligarh over 5 years. The final analysis included 187 patients who full filled the inclusion criteria, consisting of availability of whole-spine MRI and confirmation of vertebral TB. Diagnosis of NMLST was considered when other vertebral lesions were identified in addition to the primary vertebral disease, with the lesions separated by at least one normal spinal segment. The primary site was defined as the site for which the patient had been referred for MRI. RESULTS: NMLST was identified in 47 of 187 patients investigated using whole-spine MRI. The incidence was 25.1%, which was higher than that in earlier reports where whole-spine MRI was not routinely performed. The lumbar spine was involved in 37 patients, thoracic spine in 25, cervical spine in 16, and sacrum in five patients. Combined lumbar spine and thoracic spine involvement was observed in 19 patients. Thirteen patients had lumbar and cervical spine involvement, nine had thoracic and cervical spine involvement, four had combined lumbar and sacral spine involvement, and the remaining two had thoracic and sacral spine involvement. CONCLUSIONS: Tubercular spondylitis may affect the spine at multiple noncontiguous sites with the majority of additional affected sites remaining asymptomatic. Routine whole-spine MRI using all recommended sequences is not cost-effective and hence not feasible. Therefore, we recommend whole-spine screening using STIR or fat-suppressed T2W FSE sequences in all patients with suspected spinal TB. This screening is cost-effective compared with full-protocol MRI and detects additional cases of NMLST over conventional practice.